Alterations of Astrocytes in the Context of Schizophrenic Dementia - Tarasov, Vadim V.; Svistunov, Andrey A.; Chubarev, Vladimir N.; Sologova, Susanna S.; Mukhortova, Polina; Levushkin, Dmitrii; Somasundaram, Siva G.; Kirkland, Cecil E.; Bachurin, Sergey O.; Aliev, Gjumrakch (Frontiers in Pharmacology, 2020)
The levels of the astrocyte markers (GFAP, S100B) were increased unevenly in patients with schizophrenia. Reactive astrogliosis was found in approximately 70% of patients with schizophrenia. The astrocytes play a major role in etiology and pathogenesis of schizophrenia. Astrocytes produce the components that altered in schizophrenia extracellular matrix system which are involved in inflammation, functioning of interneurons, glio-, and neurotransmitter system, especially glutamate system. Astrocytes activate the interneurons through glutamate release and ATP. Decreased expression of astrocyte glutamate transporters was observed in patients with schizophrenia. Astrocytes influence on NMDA receptors via D-serine, an agonist of the glycine-binding site of NMDA receptors, and kynurenic acid, an endogenous antagonist. NMDA receptors, on its turn, control the impulses of dopamine neurons. Therefore following theories of schizophrenia are proposed. They are a) activation of astrocytes for neuroinflammation, b) glutamate and dopamine theory, as astrocyte products control the activity of NMDA receptors, which influence on the dopamine neurons.